2022
DOI: 10.3389/fcvm.2021.770228
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Two Myxomas of Different Echodensities on Transthoracic Echocardiography in One Patient

Abstract: We report a rare case of coincidental left atrial and right ventricular myxomas manifesting as masses with different echodensities on transthoracic echocardiography. This patient had a history of left atrial myxoma, left intra-left internal carotid artery myxoma, and facial cutaneous myxoma 3 years prior to admission. A Carney complex was suspected, and the patient subsequently tested positive for PRKAR1A mutations. The patient was followed up regularly by a biannual echocardiography, which was free from abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Dr. Ding's study (4) reviewed a singleinstitute 12 years of experience, which showed myxoma often occurs in elder children. CM has a familial predisposition, and approximately 10% are associated with Carney syndrome with a high recurrence rate (37,38). There is predominance in female, with the incidence ranging from 1.5 to 2 times that in men (39).…”
Section: Cardiac Myxomamentioning
confidence: 99%
“…Dr. Ding's study (4) reviewed a singleinstitute 12 years of experience, which showed myxoma often occurs in elder children. CM has a familial predisposition, and approximately 10% are associated with Carney syndrome with a high recurrence rate (37,38). There is predominance in female, with the incidence ranging from 1.5 to 2 times that in men (39).…”
Section: Cardiac Myxomamentioning
confidence: 99%